Pelatihan Kewirusahaan Bagi Pemuda di Desa Lokki Kecamatan Huamual Kabupaten Seram Bagian Barat : Pengabdian - Leiwakabessy, Erly; Siahainenia, Silfiena (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Entrepreneurship is the ability to develop one's potential by utilizing available opportunities. Entrepreneurial activities for the youth in Lokki Village, Huamual Subdistrict, West Seram Regency, were carried out with the aim of motivating them to become entrepreneurs by making use of the natural resources available in their village. The materials provided included entrepreneurship, business management, and basic bookkeeping, accompanied by discussion sessions.The results of this activity showed that the youth began to broaden their perspectives — realizing that employment is not limited to becoming civil servants. Through entrepreneurship, they can also improve their personal well-being, as well as that of their families and the surrounding community.